Circulating miRNAs miR-34a and miR-150 associated with colorectal cancer progression - Aherne, Sinéad T; Madden, Stephen F; Hughes, David J; Pardini, Barbara; Naccarati, Alessio; Levy, Miroslav; Vodicka, Pavel; Neary, Paul; Dowling, Paul; Clynes, Martin (BMC cancer, 2015)
BACKGROUND: Screening for the early detection of colorectal cancer is important to improve patient survival. The aim of this study was to investigate the potential of circulating cell-free miRNAs as biomarkers of CRC, and their efficiency at delineating patients with polyps and benign adenomas from normal and cancer patient groups. METHODS: The expression of 667 miRNAs was assessed in a discovery set of 48 plasma samples comprising normal, polyp, adenoma, and early and advanced cancer samples. Three miRNAs (miR-34a, miR-150, and miR-923) were further examined in a validation cohort of 97 subjects divided into the same five groups, and in an independent public dataset of 40 CRC samples and paired normal tissues. RESULTS: High levels of circulating miR-34a and low miR-150 levels distinguished groups of patients with polyps from those with advanced cancer (AUC = 0.904), and low circulating miR-150 levels separated patients with adenomas from those with advanced cancer (AUC = 0.875). In addition, the altered expression of miR-34a and miR-150 in an independent public dataset of forty CRC samples and paired normal tissues was confirmed. CONCLUSION: We identified two circulating miRNAs capable of distinguishing patient groups with different diseases of the colon from each other, and patients with advanced cancer from benign disease groups.
Keywords: Gene Expression Regulation, Neoplastic; Male; MicroRNAs; kolorektální nádory; Colonic Polyps; progrese nemoci; mikro RNA; regulace genové exprese u nádorů; Diagnosis, Differential; Aged; mužské pohlaví; senioři; Disease Progression; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; Early Detection of Cancer; Adenoma; diferenciální diagnóza; polypy tlustého střeva; Colorectal Neoplasms; adenom; Female; lidé středního věku; nádorové biomarkery; časná detekce nádoru; Middle Aged